The definition of subsidy and state aid WTO and EC law in comparative perspective - Rubini, Luca. (Oxford : Oxford University Press, 2010)
Presenting a conceptual analysis of the definitions of state aid and subsidy in EC and WTO law, this text provides a comparative analysis of the regulation of subsidy in both systems. Rubini examines the coherence of the conceptual understanding of subsidy and the grounds for legitimate state intervention.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Subsidies -- Law and legislation